Penerapan Metode PROMETHEE Pada Sistem Pendukung Keputusan Penentuan Sekolah Dasar Negeri Terbaik Kecamatan Rembang: Penerapan Metode PROMETHEE Pada Sistem Pendukung Keputusan Penentuan Sekolah Dasar Negeri Terbaik Kecamatan Rembang - Rozak, Abdul; Rahardiyanto, Panca; Bustomy Abdul Latif, Mukhammad Akhmad (Jurnal Sistem Informasi Aplikasi Teknologi Informasi, 2024)
Abstract: This study aims to rank the best public elementary schools in the Rembang sub-district using the Preference Ranking Organization Method for Enrichen Evaluation (PROMETHEE) method. Decision support for this system has criteria called multi criteria. Pasuruan district education office runs a program to select the best public elementary schools. The best schools will receive a reward from the service and become an example for other schools. By using the PROMETHEE method which has multiple criteria, it is hoped that the selection of the best public elementary school on the basis of various criteria can be able to select or overcome problems so that it can determine the best public elementary school in the Rembang sub-district. The expected result is that there is a web application that can help agencies and supervisors to make it easier to select and determine the criteria for making the best school.